2019
DOI: 10.3389/fpsyg.2019.01520
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Physical Activity on Bullying

Abstract: Relationship problems among school children can lead to bullying situations. In this regard, it should be noted that, among healthy lifestyle habits, sports practice (non-competitive) promotes responsibility and improves coexistence. The objective of the present study was to analyze the incidence of the frequency of practice of healthy physical activity on the risks of students directly involved in school bullying (harasser and victim) by gender. The participants of the study were 1,248 students of Compulsory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
4
22
0
4
Order By: Relevance
“…All studies included males and females (51.8% females). Twelve studies included only adolescents (12–18 years old) [ 19 , 20 , 24 , 27 29 , 31 , 32 , 34 – 37 ] and the remaining studies included both children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies included males and females (51.8% females). Twelve studies included only adolescents (12–18 years old) [ 19 , 20 , 24 , 27 29 , 31 , 32 , 34 – 37 ] and the remaining studies included both children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Being physically active for at least 60 min/day on 0 of the past 7 days was associated with having been a victim of both kinds of bullying among male students but not female students Race/ethnicity and grade 8 Katapally 2018 [ 27 ] Canada 44,861 / 13–18 years / 49.4 T, CY Self-reported Bullying perpetration, victimization, or both are associated with increased multiple screen-time behaviors among youth Age, ethnicity, weekly disposable income, daylight hours, and weather variables 8 Kelishadi 2015 [ 28 ] Iran 14,880 / 6–18 years/ 49.2 T Self-reported Prolonged time spent watching TV or using a computer for pleasure may increase the risk of being bullied. Socioeconomic status, physical activity, sleep hours, family size and body mass index 8 Mendez 2019 [ 29 ] Spain 1248 / 11–18 years / 50.8 T Self-reported Students who practiced physical activity in the recommended frequency rated as healthy, at least four or more times per week, had higher values in the indicators of aggressiveness than students who practiced with a lower frequency Not mentioned 7 Merrill and Hanson 2016 [ 30 ] USA 13,583 / 12–18 years / 48.7 T, CY Self-reported TV and video game playing Protective behaviors against bullying victimization and cyberbullying included being physically active. In contrast, students who play video games an average of 3 or more hours per day are at greater risk of being bullied and cyberbullying Sex, race/ethnicity, and grade 8 Rech 2013 [ 31 ] Brazil 1230 / 11–14 years / 49.3 T Sitting-time The schoolchildren who reported sedentary habits for more than three hours a day were 55% more likely to be victims Not mentioned 8 Roman 2013 [ 32 ] USA 7786 / 10–17 years / Not mentioned T Self-reported Students who reported being bullied ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there was no relationship between technology disorders and the incidence of underweight in this study. Previous research has suggested that bullying is positively and significantly correlated with all adverse health or psychological problems except physical inactivity and underweight (Méndez, Ruiz Esteban, & Ortega, 2019;Pengpid & Peltzer, 2019).…”
Section: Resultsmentioning
confidence: 99%